Mathematical analysis and stability in a predator-prey model - Simpe-Laura, Joseph Wilmer (2025)
In this work, we establish the way to protect a species (prey) affected by its hunter (predator), using a system of differential equations that models population dynamics. The analysis of this model leads us to guarantee the existence and unique ness of its solutions and through the stability of the system we obtain the conditions for these solutions to be adequate.